Information on dental prostheses use and bone resorption in older adults - Emily Sarahy Santana Moya; Danna Sharick Tello Nazareno; Jaime Fernando Armijos Moreta; Silvia Marisol Gavilánez Villamarín (Medisur)
Background: total or partial prostheses are a rehabilitation process for toothless patients, whether they are fixed or removable prostheses. Objective: to determine the information the older adults have on the dental prostheses and bone resorption use. Methods: cross-sectional descriptive observational study carried out from January to May 2022. 420 inhabitants of the Santa Rosa cooperative was the universe and 50 adults over 65 years of age from the El Buen Pastor church was the sample, selected by simple random sampling. The studied variables were: information on bone resorption, presence of dental prosthesis, information on the therapeutic option to be used when a tooth is missing, utensils used for daily oral hygiene, frequency of brushing and visiting the dentist. Results: most of the older adults do not have information about bone resorption. More than half have dental prostheses. 50 % prefer to use fixed prostheses as the best option in the absence of a dental piece and 75 % recognize the importance of tooth brushing to avoid contracting any disease. The seventh part considered that for oral hygiene it was only necessary to use toothpaste and a brush. Most recognized the importance of brushing their teeth after each meal and attending the dentist every six months for a preventive check-up. Conclusions: timely diagnosis and adequate information on oral health problems in older adults is of vital importance in health education.